ASPECT ANALYSIS OF KJK ORGANIZATIONAL AND MANAGEMENT POLICIES ON THE SMOOTH MANAGEMENT OF THE ARCHIPELAGO COOPERATIVE (KOPNUSPOS) LHOKSEUMAWE BRANCH - Ernanda Manurung, Fachrunnisa; Aulia, Adha; Evika, Selvi; Tussaadah, Laila; Saharuddin, Saharuddin (RADJA PUBLIKA, 2023)
In the growth and development of cooperatives that experience situations that are not conducive in its implementation due to a lack of skills and abilities in managing cooperatives on the policies and management that have been created. This paper aims to find out how the Aspects of Organizational Completeness in Nusantara Cooperatives (Kopnuspos), Management Completeness Aspects in Nusantara Cooperatives (Kopnuspos), and Identification of Policy Data in Nusantara Cooperatives (Kopnuspos). Data analysis in this study was carried out by searching for and systematically compiling the data obtained using direct interview techniques with heads of cooperative branches and documentation such as video/audio recordings. Based on the results, there is Aspects of organizational completeness consist of Cooperative Legal Entities, Organizational Structures, and Organizational Administration Books. Aspects of Management Completeness consisting of cooperative AD/ART, Work Programs, Cooperative Business Products, Business Strategy, HR Qualifications and KJK Managers, and Facilities and Infrastructure for Data Identification Policy consists of Policies Related to Membership, Policies Related to Employees, Policies Related to Business Partners, Policies Related to Operations, CSR related policies. The KJK organizational and management policy aspects that have been determined by Kopnuspos greatly facilitate optimal management of cooperative activities.